Holocene coastal landscape development in response to rising sea level in the Central Wadden Sea coastal region. (30th April 2021) - Karle, Martina; Bungenstock, Friederike; Wehrmann, Achim
Abstract: The Holocene sea-level rise has led to significant changes in present-day coastal zones through multifold retrogradational and slightly progradational displacements of the mainland coastline. During the course of this postglacial transgression, sediments characteristic of coastal environments accumulated first in palaeovalleys of the pre-Holocene landscape and later on the subsequently developed coastal plain. Based on a compilation of sedimentological, lithological and litho-chronostratigraphical data of more than 1200 sediment cores, we generated four palaeogeographic maps of the coastal zone of the central Wadden Sea to document with a high spatial resolution the landscape changes during characteristic phases of the Holocene sea-level rise, i.e. the periods 8600–6500 cal BP, 6500–2700 cal BP, 2700–1500 cal BP and 1500–1000 cal BP. Along three cross-sections, representing different hydrodynamic conditions and exposure, we exemplify how the Holocene landscape development and sedimentary facies types are controlled by the local palaeorelief, sea-level changes, sediment supply, accommodation space, the morphodynamic impact of channel shifts, and their erosion base. This leads to a better understanding of main factors controlling the local depositional processes of the coastal landscape along the central Wadden Sea during the Holocene transgression.